GLOBALIZATION AND TEACHER DEVELOPMENT FOR SPOKEN ENGLISH INSTRUCTION - Goh, Christine C.M. (Universitas Pendidikan Indonesia, 2013)
Abstract: The impact of globalization is experienced most strongly in business and commerce but also increasingly in education. As a result, some scholars have called for a re-envisioning of the role of teachers to model what it means to be a global citizen. In this paper, I acknowledge the need for ESL/EFL teachers to re-examine their identity and roles in light of these global developments. At the same time, I argue that teachers should not lose sight of the importance of honing the craft of teaching English so as to increase their professional capital to mediate the impact of globalization for their students. This article first discusses the changing roles of teachers in a globalized world and highlights the implications for English language teaching and learning.Â The ideas are further related to teaching second language oracy (speaking and listening) because of its centrality in developing important 21st Century skills in the globalized world. The article also offers ways in which teacher education that takes cognizance of globalization forces can develop ESL/ EFL teachersâ€™ knowledge and beliefs to play their new roles more effectively.